Analisis Pola Persebaran dan Keterjangkauan Fasilitas Kesehatan Kawasan Perkotaan Di Kabupaten Minahasa Utara - Mandang, Pretty; Warouw, Fela; Takumansang, Esli (Universitas Sam Ratulangi, 2024)
Healthcare facilities play a crucial role in maintaining community welfare, including handlingaccidents. Throughout 2023, there were 148,307 recorded accidents in Indonesia, with a significantincrease in North Minahasa Regency, reaching 399 cases from 301 cases in 2022. This regency israpidly developing, with the population increasing from 200,217 people in 2017 to 229,368 people in2022, and built-up areas expanding from 3% in 2011 to 10% in 2019. This growth underscores theurgent need for adequate and accessible healthcare facilities, especially considering its strategic locationbetween Manado City and Bitung City, which increases traffic and accident risks. The methods used inthis study are spatial and descriptive. Spatial methods include Nearest Neighbour Analysis to identifythe distribution pattern of healthcare facilities, as well as Buffering and Network Analysis to determinehealthcare accessibility. Descriptive methods are used to explain the results of the spatial analysis. Thestudy results show that the distribution pattern of healthcare facilities in North Minahasa Regency israndom. Each sub-district already has healthcare facilities, although they are not evenly distributed. Interms of accessibility, Kalawat, Airmadidi, and Kauditan sub-districts are well-served and have quicktravel times to healthcare facilities. Conversely, Kema sub-district is not fully served and has relativelylong travel times.Keywords: Distribution Pattern, Accessibility, Healthcare Facilities